Detection of fraudulent financial reporting trough the Crowe’s Fraud Pentagon Theory in primary consumer goods indexed - Maulida Dwi Kartikasari; Sumarno Sumarno; Rizki Nur Fitriani (Jurnal Ekonomi Modernisasi, 2021)
The purpose of this study was to determine the fraud pentagon in detecting fraudulent financial statements. The data was collected by using the documentation method, while the data analysis used was descriptive analysis, classical assumption test, and hypothesis testing. The population in this study were companies IDX Industrial Classification Food and Beverage Sub-Sector listed on the Indonesia Stock Exchange (BEI) 2016-2019. The sample in this study was 11 companies selected by the purposive sampling method. Based on the multiple linear regression analysis, the results show that opportunity, rationalization, and arrogance have a significant positive effects on fraud detection in Primary Consumer Goods Indexed. This means that rationalization, opportunity, and arrogance can detect fraudulent financial statements. However, the pressure and competence variables have a significance value below 5%. This means that the two variables do not have a significant effect on the detection of fraudulent financial reporting in companies indexed by primary consumer goods in the food and beverage sub-sector.